2020
DOI: 10.1186/s12885-020-06841-1
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab plus modified docetaxel-cisplatin-5-fluorouracil (mDCF) regimen versus mDCF in patients with metastatic or unresectable locally advanced recurrent anal squamous cell carcinoma: a randomized, non-comparative phase II SCARCE GERCOR trial

Abstract: Background: Modified docetaxel, cisplatin, and 5-fluorouracil (mDCF) regimen has become a new standard for the treatment of metastatic or unresectable locally advanced recurrent squamous cell carcinoma of the anus (SCCA) after demonstrating improved efficacy (12-month PFS of 47%) in the Epitopes-HPV02 trial. Antibodies targeting the checkpoint inhibitor (CKI) programmed cell death protein-1 (PD1) have demonstrated the efficacy as monotherapies in second-line treatment of SCCA. The aim of this study is to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…[17][18][19] To date, a 10 journals.sagepub.com/home/tam randomized phase II SCARCE trial is already ongoing to evaluate the interest of mDCF regimen in association with an anti-PD-L1 antibody. 20 In summary, DCF is so far the best evidencebased chemotherapy regimen in advanced SCCA. Updated results of Epitopes-HPV01 and 02 study, as well as its pooled analysis, confirm mDCF as the regimen of choice in patients with advanced SCCA.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] To date, a 10 journals.sagepub.com/home/tam randomized phase II SCARCE trial is already ongoing to evaluate the interest of mDCF regimen in association with an anti-PD-L1 antibody. 20 In summary, DCF is so far the best evidencebased chemotherapy regimen in advanced SCCA. Updated results of Epitopes-HPV01 and 02 study, as well as its pooled analysis, confirm mDCF as the regimen of choice in patients with advanced SCCA.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DCF to deplete MDSC in some patients while generating hTERT restricted TH1 immune response established the rational to combine this chemotherapy with PD-1 neutralization by an inhibitor of PD-L1 in HPV-driven cancers. Such enticing approach is currently under investigation (A Study of mDCF in Combination or Not With Atezolizumab in Advanced Squamous Cell Anal Carcinoma (SCARCE), NCT03519295) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immune biomarker data of Epitopes-HPV01 and -HPV02 trials showed that DCF is a good backbone chemotherapy to combine with anti-PD1/L1 since it increases antitumor human telomerase (hTert) immunity and decreases MDSC, two major factors significantly correlated with prognosis [10,24]. The association of DCF and an anti-PD1/L1 is feasible, with no particular safety signal in SCARCE trial in the metastatic setting, which evaluated DCF with or without atezolizumab [21]. The phase II INTERACT-ION is now ongoing to evaluate the efficacy and safety of DCF with ezabenlimab, an anti-PD1 antibody, as neoadjuvant treatment in stage III SCCA patients treated with CRT (NCT04719988).…”
Section: Locally Advanced Disease: Time To Shift the Paradigm?mentioning
confidence: 99%
“…To date, three randomized clinical trials are ongoing to evaluate the efficacy of a taxane-based chemotherapy with an anti-PD1/L1. The SCARCE phase II trial with mDCF+/−atezolizumab has finished its recruitment, and the final results are pending [21]. Moreover, POD1UM-303 double-blinded phase III trial with CP in combination with retifanlimab or placebo is ongoing (NCT04472429), as well as an NCI open-label phase III trial with CP+/−nivolumab (NCT04444921).…”
Section: Advanced Disease: Time For Immunotherapy-based Combinationsmentioning
confidence: 99%
See 1 more Smart Citation